KAPASITAS ASIMILASI BAHAN PENCEMAR DI MUARA SUNGAI BATANG ARAU (MUARA PADANG), SUMATERA BARAT - WIKE AYU EKA PUTRI (Akuatik: Jurnal Sumberdaya Perairan, 2007)
Batang Arau River and Muara Padang has many activities of human being such as agriculture, resident, hospital and anchorage. At the end, this condition will disturb biota lifecycle and environment esthetics. In fact, goverment of Padang Town has planned Muara Padang as a center of tourism in Padang. The purpose of this research is to find assimilative capacity of Muara Padang to receive pollutan matter. The pasut type of Muara Padang is semidiurnal tides and a analisys of mix process show that Muara Padang as partially mixed estuary. The condition of assimilative capacity in Muara Padang is still good. This condition can be described from the value some parameters (TSS, NO3, NH3, and PO4 ) that is still under loading capacity value of Muara Padang in receive pollutant load at tide time. It is becaused of dynamic hydrodynamic condition and quickly rellative time of flushing (6,832 days or 53 times/year) until loading pollutan in estuary can be sent to ocean and mixed.